ae-yd=y*y

Simple and best practice solution for ae-yd=y*y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for ae-yd=y*y equation:


Simplifying
ae + -1yd = y * y

Multiply y * y
ae + -1dy = y2

Solving
ae + -1dy = y2

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add 'dy' to each side of the equation.
ae + -1dy + dy = dy + y2

Combine like terms: -1dy + dy = 0
ae + 0 = dy + y2
ae = dy + y2

Divide each side by 'e'.
a = de-1y + e-1y2

Simplifying
a = de-1y + e-1y2

See similar equations:

| (-3x-6)(x-1)=0 | | a+0+y+d+e=d(0) | | -5x(5x-5)= | | x+(-7)=-15 | | 5(x-3)-2(x+4)=(x-3)+4(x-1) | | a^4-a^2+5=0 | | 3(x+8)=38-4x | | cos3y=1/2 | | 3x^2+41x-170=0 | | X-(2x+5)=-2(x+4)+19 | | -(2x+5)=2(x+4)+19 | | 60x/120x | | 4(x+4)=2(x+20) | | -8(3y+5)+y=-1 | | 25x+20=5x+40 | | 6x+18=-10 | | 2(-2y+5)-y=-5 | | 3(1.8+-0.4y)-y=8 | | 3y+25=2y+50 | | logy=alogx+b | | 9+-4y=9-4y | | -6x-5y=1 | | 4+3y-3y=4 | | 9n+68=7n+2n-2 | | 0=-4-4x-3x^2 | | 19+(-4y)+4y=19 | | 9x+1=3x-7 | | 9x+1=3x-1 | | 3(4+-2y)+4y=10 | | Y=-4/7x-1/7 | | 15x^2+40x-5=0 | | log(x)=0.40338 |

Equations solver categories